Evaluation of the Effectiveness of Er:YAG Laser and Conventional Periodontal Treatment in a Patient with Acute Streptococcal Gingivitis: A 2-Year Follow-Up - KADİR, TANJU (MARY ANN LIEBERT, INC, 2010)
Objective:The aim of this study was to evaluate the effectiveness of Er:YAG laser and conventional periodontal therapy in the treatment of acute streptococcal gingivitis both clinically and microbiologically. Background Data:This case report describes a 2-year follow-up of a 30-year-old, female, chronic periodontitis patient, presenting severe gingival inflammation, sensitivity, pain, and acute gingival lesions that were treated with Er:YAG laser and conventional hand and ultrasonic instruments. Materials and Methods:Before the initial periodontal treatment, microbiological samples were taken from the lesion sites with sterile paper points from the sulcuses bilaterally, and excisional biopsies were obtained from the lesions. Following diagnostic tests, the lesions were identified as acute streptococcal gingivitis. Following the measurement of clinical indices, initial periodontal therapy was performed with Er:YAG laser on the right side and conventional hand and ultrasonic instruments on the left side, which were performed as two sessions at weekly intervals. As an adjunct to mechanical periodontal therapy, 500 mg amoxicillin was prescribed t.i.d. for a week. Results:Microbiological samples grew mostly Streptococcus sp. and black pigmented obligate anaerobic bacteria. The histopathological examination revealed acanthosis, papillomatosis, and spongiotic lesions in the keratinized stratified squamous epithelium; infiltration of polymorphonuclear neutrophils, lymphocytes, and macrophages and plasma cells in the connective tissue; infiltration and accumulation of polymorphonuclear neutrophils in the epithelium, especially in the spongiotic lesions; and formation of microabscess-like clusters. After the initial periodontal treatment, clinical and microbiological measurements were repeated and reductions in clinical indices and the number of microorganisms were observed. Both treatment modalities gave similar results, and no recurrences were observed during the 2-year follow-up. Conclusion:Er:YAG laser seems to be promising and as effective as conventional periodontal therapy in the treatment of acute streptococcal gingivitis.
Keywords: ER-YAG LASER; ABLATION; TISSUE